Socio-Economic Impact Assessment of COVID-19 and Policy Implications for Bangladesh - Rahman, Sultan Hafeez; Razzaque, Abdur; Rahman, Jillur; Shadat, Wasel Bin (BRAC Institute of Governance and Development (BIGD), 2022)
The COVID-19 pandemic is causing unprecedented health and economic crisis for global economies, including Bangladesh. The economic and social disruption caused by the pandemic as reflected in a massive loss of human life worldwide, drastic decline in economic activities and employment, huge pressure on public health and other support services, social and physical distancing, etc. has been devastating. Since the first confirmed case of infection in March 2020, Bangladesh, like many other countries, had to consider some extraordinary measures including, amongst others, closure of all educational institutions, enforcement of economic shutdown measures and gradual reopening of economic activities, rolling out a stimulus package for business enterprises, etc. This study is motivated by the fact that understanding the economywide impact of Covid-19 has been challenging in Bangladesh. Global Trade Analysis Project (GTAP) model – a multi-region/multi-country computable general equilibrium comparative static framework – is utilized in this study to explore the potential impacts of COVID-19 induced disruptions for Bangladesh under three different alternative – low-shock, medium shock and high-shock scenarios. It outlines the transmission mechanisms through which the Bangladesh economy is being affected to assess the impact on major macroeconomic variables and sectoral outputs. These results are then incorporated into the social accounting matrix for Bangladesh to simulate the likely income and poverty effects for various types of households. This study also explores the likely impact of government support measures through the stimulus package in mitigating the adverse consequences.